2011
DOI: 10.1002/ejoc.201100234
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Phosphoryl Transfer of N‐Phosphoryl Amino Acids

Abstract: N-Phosphoryl amino acids (NPAAs) are a novel series of N-terminal-activated amino acids that act as the energy source and phosphoryl donor in intra-and intermolecular phosphoryl transfer to form "high-energy" species, such as acetyl phosphate and aminoacyl phosphates, and in the self-assembled synthesis of polypeptides under mild aqueous conditions. In this work, the chemical reactivity of N-mono(methoxyphosphoryl) glycine as a representative was investigated in detail by using a combination of the stable-isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…In the 13 C NMR spectrum, carbonyl group 17 showed a doublet signal at δ = 168.1 ppm (JCP = 8.8 Hz), due to its coupling with the neighboring phosphorus. 65 Significantly lower yields of 17 were attained with K3PO4 or with TCFH as coupling reagent (Figure 2). The reaction of acetic acid with K4P2O7 produced acetyl pyrophosphate 18 in a 50% yield, according to 31 P-NMR analysis.…”
Section: Scheme 2 Optimization Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 13 C NMR spectrum, carbonyl group 17 showed a doublet signal at δ = 168.1 ppm (JCP = 8.8 Hz), due to its coupling with the neighboring phosphorus. 65 Significantly lower yields of 17 were attained with K3PO4 or with TCFH as coupling reagent (Figure 2). The reaction of acetic acid with K4P2O7 produced acetyl pyrophosphate 18 in a 50% yield, according to 31 P-NMR analysis.…”
Section: Scheme 2 Optimization Experimentsmentioning
confidence: 99%
“…We speculated that phosphate salts could additionally contribute to the activation of the carboxyl substrate 2 via the formation of acyl phosphate intermediates containing a "high-energy" phosphoester bond, prone to easy nucleophilic amine attack. 65,66 Interestingly, the same pathway is also involved in the ATP-dependent biosynthesis of amide bond-containing biomolecules. 11 The plausibility of our assumption is further supported by existing literature showing that acyl phosphates can be indeed generated in solution by the DCC-mediated coupling of carboxylic acids with phosphate salts.…”
Section: Scheme 2 Optimization Experimentsmentioning
confidence: 99%
“…Zhang et al () reported another example for NHS esters capable of undergoing diastereomeric ICD: stable isotope N ‐phosphoryl amino‐acid labeling (SIPAL) strategy. SIPAL is based on using duplex ICD reagents, 18 O 0 ‐ and 18 O 2 ‐ N ‐diisopropyl phosphoryl L‐alanine N ‐hydroxysuccinimide esters ( 18 O 0 / 18 O 2 ‐DIPP‐L‐Ala‐NHS), which were designed and synthesized based on organic phosphorus chemistry (Gao et al, ; Ji et al, ). First, 18 O 0 / 18 O 2 ‐diphenyl phosphite was reacted with isopropanol producing 18 O 0 / 18 O 2− diisopropyl H‐phosphite ( 18 O 0 / 18 O 2 ‐DIPP‐H) by intramolecular phosphoryl transfer (Gao et al, ).…”
Section: Isotope‐coded Derivatization Reagents For Lc–ms Analysismentioning
confidence: 99%
“…SIPAL is based on using duplex ICD reagents, 18 O 0 ‐ and 18 O 2 ‐ N ‐diisopropyl phosphoryl L‐alanine N ‐hydroxysuccinimide esters ( 18 O 0 / 18 O 2 ‐DIPP‐L‐Ala‐NHS), which were designed and synthesized based on organic phosphorus chemistry (Gao et al, ; Ji et al, ). First, 18 O 0 / 18 O 2 ‐diphenyl phosphite was reacted with isopropanol producing 18 O 0 / 18 O 2− diisopropyl H‐phosphite ( 18 O 0 / 18 O 2 ‐DIPP‐H) by intramolecular phosphoryl transfer (Gao et al, ). Second, 18 O 0 / 18 O 2 ‐DIPP‐H were reacted with alanine forming 18 O 0 / 18 O 2 ‐DIPP‐L‐Ala.…”
Section: Isotope‐coded Derivatization Reagents For Lc–ms Analysismentioning
confidence: 99%
“…Trimetaphosphate (P 3 ) could have been made directly from an acidic phosphate as a byproduct of volcanic processing [ 3 , 13 ]. More recently, the structural characterization of N -phosphoryl amino acids and the formation of the P–N bond have been elucidated by NMR [ 14 ] and IR [ 15 ] analysis, which have provided significant insight into the reaction mechanism [ 16 ]. Despite quite extensive studies on the activation of amino acids by polyphosphates, little effort has been devoted to study the subsequent dehydration (or condensation) reactions resulting in polypeptide formation.…”
Section: Introductionmentioning
confidence: 99%